Simulação da gaseificação de borra oleosa de petróleo em um reator de fluxo de arraste - Mendes, Helena Carvalho (2019)
The present work analyses the viability for the reuse of oil sludge, generated during the production and processing of oil, by gasification in an entrained flow reactor. The analysis is performed using CeSFaMB ™ software, which was developed to simulate gasification processes of various products. The modeling process implemented in CeSFaMB ™ considers a detail one-dimensional and steady-state model and is based on semi-empirical correlations used to describe reactor fluid dynamics. To evaluate the gasification process, two oil sludge compositions are considered, each being analyzed for three stoichiometric ratios. Finally, it is evaluated the possibility of gasifying more than one type of sludge simultaneously, aiming to represent a real scenario of a refinery. The results allow an evaluation of the influence of parameters such as raw material composition, stoichiometric ratio and gasifier temperature.